A Study of the Correlation of Some Sex Hormone with Obesity in Women with Secondary Infertility. - Jawad, Alaa H; Ibrahim, Suhad A; Hadi, Donya M; Jawad, Zyad H (Al-Nahrain Journal of Science, 2018)
Infertility is the inability to conceive a child for more than one year. The present study indicates that the obesity associated with infertility. The aim of the study to determine follicle stimulating hormone, luteinizing hormone, testosterone hormone and prolactin levels. and cholesterol and triglyceride concentration in 2nd inferetid women. This study was carried out at kamal al-samaarai hospital the data were collected from 95 secondary infertilial women were age between 16-45 years old and grouped them in to obese (n = 46) and non obese(n = 49). There was no significant difference between the two groups (p< 0.05). Body mass index in Infertile obese women is slightly higher than non obese Infertile women which is statistically significant (P 0.05).The BMI was correlated positively with triglyceride in obese group while BMI was positive correlation highly significant with cholesterol in non obese group. Regression analysis revealed obese to be strongly associated with observed infertility. The elevated prolactin values in secondary infertile women clearly shows that there is a mechanism operating at the anterior pituitary level which shows an abnormal distribution of FSH and LH which may further explain the abnormal delay ovum maturation. This study also indicates obese associated with infertile more than non obese women.